The rare complication of vascular malformations of the limb after sclerotherapy: a report of 3 cases and brief literature review - Nianzhe Sun; Rui Liu; Gechang Cheng; Panfeng Wu; Fang Yu; Liming Qing; Lei Zeng; Xiaoyang Pang; Ding Pan; Yongbin Xiao; Umar Zeb Khan; Juyu Tang (BMC, 2023)
Abstract Background Vascular malformations are common but complicated types of disease in infants, with unclear causes and lack of effective prevention. The symptoms usually do not disappear and tend to progress without medical intervention. It is extremely necessary to choose correct treatment options for different types of vascular malformations. A large number of studies have confirmed that sclerotherapy has a tendency to become the first-line treatment in near future, but it is also associated with mild or severe complications. Furthermore, to our knowledge, the serious adverse event of progressive limb necrosis has not been systematically analyzed and reported in the literature. Case presentation Three cases (two females and one male) were presented who were all diagnosed as vascular malformations and were treated by several sessions of interventional sclerotherapy. Their previous medical records showed the use of several sclerosants in different sessions including Polidocanol and Bleomycin. The sign of limb necrosis did not occur during the first sclerotherapy, but after the second and third sessions. Furthermore, the short-term symptomatic treatment could improve the necrosis syndrome, but could not change the outcome of amputation. Conclusion Sclerotherapy undoubtedly tends to be the first-line treatment in near future, but the adverse reactions still remain major challenges. Awareness of progressive limb necrosis after sclerotherapy and timely management by experts in centers of experience of this complication can avoid amputation.